Spontaneous Lithiophilic and Lithium-Ion Conductive Functional Layer Formation Enabled by Solution-Casted Zinc Nitride for Highly Stable Lithium Metal Electrode in Carbonate Electrolyte. (11th February 2023) - Kim, Ki Jae; Leem, Han Jun; Yu, Jisang; Kim, Hyun-seung
Abstract : To improve the reversibility of the Li metal negative electrodes, the simultaneous formation of individually functionalized zinc metal and lithium nitride during the spontaneous conversion reaction of zinc nitride particle is conducted by casting of zinc nitride particles on the lithium electrode. Lithiophilic zinc metal reduces the nucleation polarization of the lithium electrode, whereas the highly ionic conductive and electronically insulating Li3 N decreases the concentration polarization from the facile ion conduction and suppression of further electrolyte decomposition during Li plating and stripping. Both these sophisticated characteristics resulted in an improvement in the deposition morphology of lithium electrode, thereby enhancing the reversibility of lithium electrode. Consequently, the cycleability improvement of Li/LiNi0.8 Co0.1 Mn0.1 O2 is achieved through the application of zinc nitride surface-treated lithium electrode.